STRATEGI PRODUKSI PROGRAM TALK SHOW BERBASIS TEKNIK MULTI-CAMERA PADA INDUSTRI PENYIARAN TELEVISI - Winda Kustiawan; Dermawan Wijaya Harahap; Nila Anggraini Nasution; Nur Hasanah; Rian Hidayat; M. Farhan Aziz (STKIP Subang, 2026)
The television broadcasting industry requires effective production strategies to produce high-quality and engaging programs. Talk shows are among the television formats that demand efficient production management and dynamic visual presentation. One production approach commonly applied is the multi-camera technique, which enables simultaneous image capture from multiple angles. This study aims to analyze production strategies for talk show programs based on multi-camera techniques in the television broadcasting industry. The research employed a literature review method using scientific journals, books, and relevant academic publications. The results indicate that successful multi-camera production depends on proper pre-production planning, effective crew coordination, strategic camera placement, and optimal use of switching systems during production. In addition, the multi-camera approach improves production efficiency, enriches visual presentation, and supports live broadcasting. Therefore, the implementation of multi-camera-based production strategies plays an important role in enhancing the quality and professionalism of television talk show programs.